การใช้พื้นที่สาธารณะในการพักผ่อนหย่อนใจ : ศึกษากรณีกลุ่มคนเล่นหมากรุกจีนในสวนลุมพินี - อภิชาติ วิวัฒนิวงศ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
To study how Chinese chess players use public space for private space and reasons why they choose Lumpini park to be their place for chess playing. It is an ethnographic research, focusing on participant observation and in-depth interview methods. The findings revealed that Chinese chess players choose Lumpini park because of its atmosphere. Lumpini park is a huge open space with lots of trees, green lawns, large lakes and animals. The park is well-designed and beautifully decorated suitable for outdoor activities. Situated at the center of Bangkok which is heavily polluted, the green park attracts many Bangkokians including Chinese chess players for its fresh air and green open space. Chinese chess players use public space as their own private space. For them, the park is like their home. The use of public space of Chinese chess players overlaps with private space. This is a unique characteristic of Thai use of public space.